2015
DOI: 10.1371/journal.pone.0128972
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Power of a Body Shape Index for Development of Diabetes, Hypertension, and Dyslipidemia in Japanese Adults: A Retrospective Cohort Study

Abstract: Background/ObjectivesRecently, a body shape index (ABSI) was reported to predict all-cause mortality independently of body mass index (BMI) in Americans. This study aimed to evaluate whether ABSI is applicable to Japanese adults as a predictor for development of diabetes, hypertension, and dyslipidemia.Subjects/MethodsWe evaluated the predictive power of ABSI in a retrospective cohort study using annual health examination data from Chiba City Hall in Japan, for the period 2008 to 2012. Subjects included 37,581… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
53
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 26 publications
(40 reference statements)
13
53
1
3
Order By: Relevance
“…For a person with a given height and weight, ABSI is suitable for reflecting VAT [14]. Excess VAT correlates with lipid and carbohydrate metabolism dysfunction [11], which is involved in the increased risk of diabetes; however, Fujita et al [21] showed that ABSI was not a better predictor of diabetes, hypertension or dyslipidaemia than BMI or waist circumference in Japanese adults. Maessen et al [15] found that ABSI was not a suitable index to identify either CVD or CVD risk factors in Dutch adults.…”
Section: Discussionmentioning
confidence: 99%
“…For a person with a given height and weight, ABSI is suitable for reflecting VAT [14]. Excess VAT correlates with lipid and carbohydrate metabolism dysfunction [11], which is involved in the increased risk of diabetes; however, Fujita et al [21] showed that ABSI was not a better predictor of diabetes, hypertension or dyslipidaemia than BMI or waist circumference in Japanese adults. Maessen et al [15] found that ABSI was not a suitable index to identify either CVD or CVD risk factors in Dutch adults.…”
Section: Discussionmentioning
confidence: 99%
“…ABSI was significantly associated with the incidence of diabetes and dyslipidemia even after adjustment for BMI, where it is predictively superior to WC after sex-and age-adjustment in Japanese adults [35]. ABSI is a weaker predictor of cardiovascular disease mortality among White Americans [36], cardiovascular disease risk factors among Asians [35] and stroke risk among Spanish European men [37]. In our controls and patients, ABSI correlated negatively with BMI and HGF.…”
Section: Discussionmentioning
confidence: 60%
“…ABSI predicted all-cause mortality independent of BMI in a large cohort of American adults during an average 4.8-year follow-up [26,31]. ABSI was significantly associated with the incidence of diabetes and dyslipidemia even after adjustment for BMI, where it is predictively superior to WC after sex-and age-adjustment in Japanese adults [35]. ABSI is a weaker predictor of cardiovascular disease mortality among White Americans [36], cardiovascular disease risk factors among Asians [35] and stroke risk among Spanish European men [37].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations